Comparison of Oral Versus Intravenous Iron Therapy in Improving Hemoglobin Status in Patients of Chronic Kidney Disease: Oral Versus Intravenous Iron Therapy for Improving Hemoglobin - Nawaz, Hamza; Rehman, Faheem Ur; Talal, Umer; Habib, Muhammad Farukh; Nawaz, Huda; Amin, Zainab; Chattha, Ali Naseem (Pakistan Journal of Health Sciences, 2024)
Anemia (particularly iron deficiency) is an important concern in patients with chronic kidney disease (CKD) as it reflects the outcome of the disease. Objective: To compare the treatment efficacy of oral versus intravenous iron supplementation in improving the hemoglobin status of patients with chronic kidney disease not on hemodialysis or erythropoietin. Methods: Randomized controlled trial was carried out in Medicine Department of Pak Emirates Military Hospital, Rawalpindi from Jun 2023 to Dec 2023. Patients in Group I received intravenous iron sucrose 200 mg once a week diluted in 500 ml of 0.9% normal saline given over 60-90 minutes. Patients in Group O received oral iron supplementation in a dose of 325 mg (containing 65 mg of elemental iron) thrice a day taken one hour before taking their meals with a glass of water. The treatment was continued for 4 weeks. Results: Mean values of serum iron were 84.41±5.56 mcg/dl in Group I versus 84.67±5.43 mcg/dl in Group O before the start of therapy (p=0.726). Serum values for iron post-therapy were 143.40±6.01 mcg/dl in Group I versus 125.35±6.68 mcg/dl in Group O (p<0.001). Mean values for serum hemoglobin were 7.74±0.74 g/dl in Group I versus 7.61±0.82 g/dl in Group O before the start of therapy (p=0.256). Serum values of Hb post-therapy were 12.31±0.71 g/dl in Group I versus 9.91±0.82 g/dl in Group O (p<0.001). Conclusions: We conclude that Intravenous (IV) iron is superior to oral iron supplementation in improving iron stores and Hb levels in CKD patients not on dialysis and/or erythropoietin